2017
DOI: 10.1002/ange.201705746
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Organocatalytic Intramolecular Aza‐Diels–Alder Reaction

Abstract: A highly efficient catalytic enantioselective intramolecular Povarov reaction was developed with primary anilines as 2‐azadiene precursors. A wide variety of angularly fused azacycles were obtained without column chromatography in high to excellent yields and with excellent diastereo‐ and enantioselectivity (d.r.>99:1 and up to e.r. 99:1). Furthermore, the catalyst loading could be lowered to 1 mol %, and the obtained azacycles could be used as key intermediates for further transformations to generate addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 65 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…We have previously demonstrated that bulky (S)-2,4,6-triisopropylphenyl 1,1'-bi-2-naphthol phosphoric acid 1 was able to efficiently promote the enantioselectivei ntramolecularP ovarov reactionb etween 2-formylphenyl 3-(4-hydroxyphenyl)acrylate derivatives 2 and 2-aminophenols 3.Awide range of 2-aminophenolsw ith electron-donating and -withdrawing groups were appropriate substrates to afford trans-trans tetrahydrochromeno[4, 3-b]quinolin-6-ones 4 with both high enantio-(98 to > 99 % ee)a nd diastereoselectivities (> 99:1 d.r.) [10] Various substituents on the aromatic ring of phenolic dienophile partners were also well tolerated. At the same time, few substituents on aromatic aldehydes were evaluated in our previous studies and werem ainly limited to bromide, methyl, and methoxy groups.I nt his context, we turned our attention to investigate other substituted salicylaldehydes,w hich possessed synthetic handles for further synthetic elaboration.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously demonstrated that bulky (S)-2,4,6-triisopropylphenyl 1,1'-bi-2-naphthol phosphoric acid 1 was able to efficiently promote the enantioselectivei ntramolecularP ovarov reactionb etween 2-formylphenyl 3-(4-hydroxyphenyl)acrylate derivatives 2 and 2-aminophenols 3.Awide range of 2-aminophenolsw ith electron-donating and -withdrawing groups were appropriate substrates to afford trans-trans tetrahydrochromeno[4, 3-b]quinolin-6-ones 4 with both high enantio-(98 to > 99 % ee)a nd diastereoselectivities (> 99:1 d.r.) [10] Various substituents on the aromatic ring of phenolic dienophile partners were also well tolerated. At the same time, few substituents on aromatic aldehydes were evaluated in our previous studies and werem ainly limited to bromide, methyl, and methoxy groups.I nt his context, we turned our attention to investigate other substituted salicylaldehydes,w hich possessed synthetic handles for further synthetic elaboration.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, we observed that the presenceo ft he 2-hydroxy group on the 2-azadiene played an important role in asymmetric induction. [10] In this context, we were then interested in investigating the influence of using other hydrogenbond donors on enantioselectivity.2 -Aminothiophenol (3b) and tert-butyloxycarbonyl (Boc)-monosubstituted 1,2-diaminobenzene (3c)w ere tested in the intramolecular Povarov reaction with 2a and 5a.S urprisingly,s ubstrate 3b appeared to be unreactiver egardless of the linear partner used, so no desired product wasi solated (4i or 6a), even at higher temperature (50 8C). However,a lthough no reactionw as observed with the linear precursor bearing an ester linker, 2a,b ulky diaminobenzene 3c reacted efficiently with 5a,w hich had an amide linker.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations